Awareness on Consequences of Teenage Pregnancy among Adolescent at Ampipal VDC, Gorkha - Bhandari, Sushila Devi (Journal of Advanced Academic Research, 2015)
Background: Teenage pregnancy is significant medical and social problem in many parts of the world. Complication of the child birth and unsafe abortion are among the main causes of death for women under 20. Early teenage pregnancy can cause severe health problems for both the mother and child. Moreover, an early start to childbearing greatly reduces women’s educational and employment opportunities and is associated with higher levels of fertility.The objective of the study was to assess awareness on consequences of teenage pregnancy among adolescent of Ampipal VDC.Methods: Cross sectional descriptive study was used as research design. Interview questionnaire tool was used as an instrument for data collection. Systematic analysis of 100 respondents of Ampipal VDC was done and chi square test and awareness regarding consequences of teenage pregnancy of study population was examined using the SPSS (16.0).Results: The study revealed that more than half (74%) had adequate knowledge on consequences of teenage pregnancy to mother and baby with mean score 12.34. More than of respondents (86%) had adequate knowledge on cause of teenage pregnancy with mean score 6.38.Conclusion: The study concluded that half of respondent (74%) had adequate knowledge on consequences of teenage pregnancy. There was statistical significance between educational level and knowledge on consequences of adolescent pregnancy whereas there was no association between knowledge and other socio demographic variables (ethnicity, family structure and occupation).Journal of Advanced Academic Research Vol.1(1) 2014: 10-17